STUDY ON THE CONSUMER ACCEPTANCE OF THE SEAWEED NORI (Echeuma cottonii) ADDED WITH CATFISH PROTEIN CONCENTRATE (Pangasius hypophthalmus) - Hasnah Dewi Nasution; Dewita Buchari; Suparmi Suparmi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT This study aimed to determine the consumer acceptance of nori added with different amounts of catfishprotein concentrate. The method used is the experimental method, and the design used was completelynon factorial random design. The treatment was the addition of catfishprotein concentrate to nori (0, 10%, and 15%). The parameters used were organoleptic value (the value of appearance, flavour, texture, and taste), and proximate composition (the content of water, ash, protein and crude fiber). The result showed that the treatment on the addition of 10% catfish protein consentrate to the seaweed (Euchema cottoni) was indicating the highest consumer acceptance.The best nori was characterized by thehighest value of sensory characteristics, those were good taste, compact texture and typical ofnori. The noricontained water 13,10%, ash 1,55%, protein 9,96%, and crude fiber 18,36%. Keywords: Fish Protein Concentrate, Organoleptic, Parameters, Proximate